Identification of responders to inhaled corticosteroids in a chronic obstructive pulmonary disease population using cluster analysis. Issue 6 (1st June 2016) - Hinds, David R; DiSantostefano, Rachael L; Le, Hoa V; Pascoe, Steven
Abstract : Objectives: To identify clusters of patients who may benefit from treatment with an inhaled corticosteroid (ICS)/long-acting β2 agonist (LABA) versus LABA alone, in terms of exacerbation reduction, and to validate previously identified clusters of patients with chronic obstructive pulmonary disease (COPD) (based on diuretic use and reversibility). Design: Post hoc supervised cluster analysis using a modified recursive partitioning algorithm of two 1-year randomised, controlled trials of fluticasone furoate (FF)/vilanterol (VI) versus VI alone, with the primary end points of the annual rate of moderate-to-severe exacerbations. Setting: Global. Participants: 3255 patients with COPD (intent-to-treat populations) with a history of exacerbations in the past year. Interventions: FF/VI 50/25 µg, 100/25 µg or 200/25 µg, or VI 25 µg; all one time per day. Outcome measures: Mean annual COPD exacerbation rate to identify clusters of patients who benefit from adding an ICS (FF) to VI bronchodilator therapy. Results: Three clusters were identified, including two groups that benefit from FF/VI versus VI: patients with blood eosinophils >2.4% (RR=0.68, 95% CI 0.58 to 0.79), or blood eosinophils ≤2.4% and smoking history ≤46 pack-years, experienced a reduced rate of exacerbations with FF/VI versus VI (RR=0.78, 95% CI 0.63 to 0.96), whereas those with blood eosinophils ≤2.4% and smoking history >46 pack-years were identified as non-responders (RR=1.22, 95% CI 0.94 to 1.58). Clusters of patients previously identified in the fluticasone propionate/salmeterol (SAL) versus SAL trials of similar design were not validated; all clusters of patients tended to benefit from FF/VI versus VI alone irrespective of diuretic use and reversibility. Conclusions: In patients with COPD with a history of exacerbations, those with greater blood eosinophils or a lower smoking history may benefit more from ICS/LABA versus LABA alone as measured by a reduced rate of exacerbations. In terms of eosinophils, this finding is consistent with findings from other studies; however, the validity of the 2.4% cut-off and the impact of smoking history require further investigation. Trial registration numbers: NCT01009463; NCT01017952 ; Post-results.